Control de concentraciones e intercambio de información en el marco de operaciones de fusión y adquisición - Felices Saavedra, Enrique (2020)
The issuance of the Emergency Decree 013-2019, which regulates market concentration operations by establishing an ex ante control of said transactions, forces us to reexamine the way in which information exchanges are conducted in the framework of mergers and adquisitions. The exchange of information is vital to this types of operations, however, it can not be unlimited, since that would endager market competition. Faced with this situation, this article analyzes the possible transgresions to this new regimen that could be comitted within these types of transactions, as well as the measures that could be implemented to reduce said risks. First, the authors explores the figures of horizontal colusion and gun jumping, by analyzing national and international legislation and jurisprudence. Then, they explain the powers Indecopi posseses to sanction these conducts. Finally, they conclude with some recommended preventive measures that can be taken by businesses.